On-surface isostructural transformation from a hydrogen-bonded network to a coordination network for tuning the pore size and guest recognition. Issue 4 (7th December 2020) - Zhou, Dong-Dong; Wang, Jun; Chen, Pin; He, Yangyong; Wu, Jun-Xi; Gao, Sen; Zhong, Zhihao; Du, Yunfei; Zhong, Dingyong; Zhang, Jie-Peng
Abstract : A hydrogen-bonded network on a Ag(111) surface can transform into an isostructural Ag(i ) coordination network, giving drastically different host–guest recognition behaviours. Abstract : Rational manipulation of supramolecular structures on surfaces is of great importance and challenging. We show that imidazole-based hydrogen-bonded networks on a metal surface can transform into an isostructural coordination network for facile tuning of the pore size and guest recognition behaviours. Deposition of triangular-shaped benzotrisimidazole (H3 btim) molecules on Au(111)/Ag(111) surfaces gives honeycomb networks linked by double N–H⋯N hydrogen bonds. While the H3 btim hydrogen-bonded networks on Au(111) evaporate above 453 K, those on Ag(111) transform into isostructural [Ag3 (btim)] coordination networks based on double N–Ag–N bonds at 423 K, by virtue of the unconventional metal–acid replacement reaction (Ag reduces H + ). The transformation expands the pore diameter of the honeycomb networks from 3.8 Å to 6.9 Å, giving remarkably different host–guest recognition behaviours for fullerene and ferrocene molecules based on the size compatibility mechanism.